Techniques for analysing android malware - Adebayo, Olawale Surajudeen; Abdul Aziz, Normaziah (IEEE, 2014)
The Android operating system is gaining market share on smartphones and tablets due to its market openness and easier accessibility and operations.Therefore, it is increasingly targeted by malware. This research examines several attack vectors on an android smartphone. Techniques are presented for the analysis of such attack vectors in order to identify and obtain useful features for analysis and classification. Suggestions are offered for appropriate solution. The research recommends appropriate practices to ensure the security of information on an android smartphone.